Assessment of the prevalence, risk factors of insomnia, and its effect on quality of life among young population of North region - Shah, Aitisam F.; Patil, R. K.; Gupta, Ramit (International Journal Of Community Medicine And Public Health, 2022)
Background: Insomnia is characterized as a complaint of inadequate sleep. Insomnia becomes a major public concern day by day which influences the quality of life of numerous individuals around the planet. The objectives of this study were to determine the prevalence and risk factors of insomnia in the general population and to determine the quality of life. Methods: It was a cross-sectional observational study. Data were obtained from the general population by using a standard questionnaire, the ISI scale, and quality of life satisfaction scales were used. Results: The prevalence rate of insomnia was 33%. A total of 88 subjects had insomnia. There was an association between insomnia and life style factors at significance p value ≤ 0.05.The associated factors were profession, education, marital status, lifestyle factors such as watching TV or phone before sleep, smoking, drinking alcohol, do not walk daily, family history of psychiatric disease, medical history, and psychiatric history. The average scoring for quality of life was about 50.34 in those who did not have insomnia as compared to 38.49 in those who had insomnia. Conclusions: A one-third of the young population had insomnia. Quality of life is impaired due to insomnia. There must be education programs for young individuals to provide the information on promoting sleep.